The determination of uric acid in the presence of ascorbic acid and dopamine using [(1H-1,2,4-triazole-3-ylimino)methyl]naphthalene-2-ol modified platinum electrode - (:unkn) unknown (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2020)
In this study, a modified electrode was developed via coating to platinum electrode (Pt) surface with a [(1H-1,2,4-triazole-3-ylimino)methyl]naphthalene-2-ol (TMN-2-ol) film. Deposition of TMN-2-ol was performed by cyclic voltammetry scanning from -0.8 V to +2.0 V at a sweep rate of 100 mV s(-)(1) for 40 cycles in 1 x10(-3) M TMN-2-ol solution. The modified electrode was characterized by cyclic voltammetry (CV), reflection adsorption infrared spectroscopy (RAIRS) and contact angle measurements (CAM). The electrocatalytic activity of the prepared and characterized modified electrode against UA in the presence of ascorbic acid (AA) and dopamine (DA) was determined by square wave voltammetry (SWV). The optimum working conditions were determined such as supporting electrolyte, pH. It was found that, the appropriate supporting electrolyte medium was 0.1 M pH 7.2 phosphate buffer (PBS). The calibration curve and limit of detection (LOD) were obtained in the range of 1.23 x 10(-6)-1.51x 10(-5) M and 1.56 x10(-8) M at the TMN-2-ol/Pt electrode, respectively. The effects of various anions and cations on the peak current of UA were investigated. The UA analysis was performed in human serum with low relative standart deviation values at the modified electrode by standard addition method.
Keywords: Electrode modification; reflection adsorption infrared spectroscopy; square wave voltammetry; platinum electrode; uric acid; GLASSY-CARBON ELECTRODE; SELECTIVE DETERMINATION; ELECTROCHEMICAL DETERMINATION; VOLTAMMETRIC DETECTION; GOLD ELECTRODE; SENSOR; FILM